Pelatihan penggunaan mail merge untuk efisiensi pengelolaan surat disposisi pada Dinas Sosial Bagian Umum - Hastuti, Kartika; Rodi, Muhamad (Penamas: Journal of Community Service, 2025)
This community service activity aims to improve employees' competencies in managing digital-based disposition letters in the General Division of the Social Affairs Office. The main problem is that disposition letters are still recorded and retrieved manually, resulting in lengthy processing times when searching older archives. The activity was conducted on Monday, September 15, 2025, with five employees participating. The implementation method included pre-test, training, and post-test stages, using a hands-on (learning-by-doing) approach. The results showed a significant improvement in participants' abilities after the training. Based on the post-test results, all participants achieved scores in the "excellent" category (76–100), which initially ranged from "fair" (26–50). This activity has proven effective in increasing work efficiency and employees' digital skills, and it can serve as a training model for technology-based administrative letter management within government institutions.